Fractalkine regulation of microglial physiology and consequences on the brain and behavior - Paolicelli, Rosa Chiara; Bisht, Kanchan; Tremblay, Marie-Ève (Frontiers in Cellular Neuroscience, 2014)
Neural circuits are constantly monitored and supported by the surrounding microglial cells, using finely tuned mechanisms which include both direct contact and release of soluble factors. These bidirectional interactions are not only triggered by pathological conditions as a S.O.S. response to noxious stimuli, but they rather represent an established repertoire of dynamic communication for ensuring continuous immune surveillance and homeostasis in the healthy brain. In addition, recent studies are revealing key tasks for microglial interactions with neurons during normal physiological conditions, especially in regulating the maturation of neural circuits and shaping their connectivity in an activity- and experience-dependent manner. Chemokines, a family of soluble and membrane-bound cytokines, play an essential role in mediating neuron-microglia crosstalk in the developing and mature brain. As part of this special issue on Cytokines as players of neuronal plasticity and sensitivity to environment in healthy and pathological brain, our review focuses on the fractalkine signalling pathway, involving the ligand CX3CL1 which is mainly expressed by neurons, and its receptor CX3CR1 that is exclusively found on microglia within the brain. An extensive literature largely based on transgenic mouse models has revealed that fractalkine signalling plays a critical role in regulating a broad spectrum of microglial properties during normal physiological conditions, especially their migration and dynamic surveillance of the brain parenchyma, in addition to influencing the survival of developing neurons, the maturation, activity and plasticity of developing and mature synapses, the brain functional connectivity, adult hippocampal neurogenesis, as well as learning and memory, and the behavioural outcome.